KETIDAKPASTIAN LINGKUNGAN BISNIS PENGARUHNYA DALAM BUDAYA ORGANISASI - Purwanto, Arief - (JURNAL MANAJEMEN DAN AKUNTANSI, 2013)
Abstract:The aims of this study are to examine and prove empirically the role of uncertainty business environment to organizational culture of Islamic Commercial Banks (Bank Umum Syariah/BUS). This research is an explanative study which examines and explains the research variables in cross-sectional manner. Quantitative approach was used as the main analytical method and supported by qualitative approach. The population of the study was all BUS branch offices located in East Java, as many as 34 branch offices. All BUS branch offices in East Java were used as sample; thus, this study is a census study and analyzed using Partial Least Square (PLS) with SmartPLS software.The results of the study indicate that: The business environment provide a significant impact on improvinga stronger organizationalculture. Keywords:Uncertainty business environment, organizational culture.